Challenges and opportunities of indigenous dairy production and management: The case of selected rural villages in Bambasi District, Benishangul Gumuz Regional State, Western Ethiopia - Fekadu Begna (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
The data sources were both primary and secondary data. To enable an analysis of data collected through questionnaire, Statistical Package for Social Sciences (SPSS) software (version 20) was used. The mean family size of the respondents was 6.04. The mean and SDs of cattle holding per household was (8.38±4.91). The total (67.9%) of respondents were having not have owned grazing land for their dairy cows. Tryponomiasis disease (Gendi) ranked first, Pasteurellosis disease second, and external parasites were third. (98.2%) respondents rear indigenous breeds. The mean daily milk production per cow was 1.4 liters. More than half of the milk was used for family consumption. Milk is sold in the area through an informal market directly to the retailer. Technical strategies to support smallholder cattle production should focus on improving technical and institutional constraints by providing adequate veterinary services, improving fodder cultivation, proper crop residue management, and improvement, supplying medical equipment and medicines, adequate extension service, improved water availability, and improving breeding systems. To ensure a reliable feed supply throughout the year, fodder conservation practices, especially hay and crop residues, should be encouraged.